Subclinical autistic traits mediate the relationship between emotional intelligence and resiliency in adolescents. (1st May 2020) - McCarthy, Shannon A.; Ford, Talitha C.; Lomas, Justine E.; Stough, Con
Abstract: Individuals with autism and those with high subclinical autistic traits often report poor trait emotional intelligence (EI) and psychosocial outcomes. EI predicts resiliency in adolescents, however, the interrelationship between autistic traits, EI and resiliency is unknown. The Adolescent Swinburne University EI Test, Autism-Spectrum Quotient (AQ) and Resiliency Scales for Children and Adolescents were completed by 212 adolescents (193 males; 14–17 years). In line with previous studies, adolescents with better EI reported more resiliency, and fewer autistic traits, while fewer autistic traits were associated with better resiliency. Mediation analyses revealed that the relationships between EI dimensions and resiliency were partially or fully mediated by AQ Social Skills and AQ Communication, suggesting that trait EI is an important predictor of resiliency, but that these autistic trait dimensions drive this relationship. The findings have significant implications for developing EI programs that foster resiliency in adolescents across the clinical and subclinical autism spectrum.